Wattpad as a Catalyst for English Writing Development: An Explorative Study on Student Perceptions - Helda, Nur Fadilah; Thohirah, Afifah (English LAnguage Study and TEaching, 2023)
Wattpad has emerged as a valuable tool in English language education, particularly for enhancing writing skills. Previous studies highlight Wattpad's efficacy in improving writing style, creativity, and students' motivation to write. This platform offers diverse genres and features, enabling writers to share their work and engage with a global audience. Despite its impact on writing skills; enhancing grammar, vocabulary, and structure there's a gap in understanding students' perceptions regarding Wattpad's role as a teaching tool, specifically in writing. Utilizing a qualitative approach with interviews, this research explores the perceptions of five English Education students at Serambi Mekkah University. Their insights highlight Wattpad as a space for regular writing practice, an assisting tool in refining language skills, storytelling and character development. The participants express that the Interactions with readers provide them with valuable feedback, and enrich their understanding of their craft. While Wattpad influences motivation and writing proficiency, it does not significantly impact students' reading interests. This research contributes to understanding Wattpads multifaceted role in language education, offering insights into its implications for writing development and broader exposure to diverse written works.